Design of nonuniform near allpass complementary FIR filters via a semi-infinite programming technique - Ho, C.Y.F.; Ling, B.W.K.; Liu, Y.; Tam, P.K.S.; Teo, K.L. (IEEE transactions on signal processing, 2005)
In this correspondence, we consider the problem of designing a set of nonuniform near allpass complementary finite impulse response (FIR) filters. This problem can be formulated as a quadratic semi-infinite programming problem, where the objective is to minimize the sum of the ripple energy for the individual filters, subject to the passband and stopband specifications as well as to the allpass complementary specification. The dual parameterization method is used for solving the linear quadratic semi-infinite programming problem.